2013
DOI: 10.1093/jjco/hyt125
|View full text |Cite
|
Sign up to set email alerts
|

Hypertriglyceridemia is Frequent in Endometrial Cancer Survivors

Abstract: ObjectivePrevious studies have reported an association between endometrial cancer and the risk of metabolic syndrome; however, the pattern of endometrial cancer-associated dyslipidemia is not well understood. The standard therapy for endometrial cancer is total abdominal hysterectomy and bilateral salpingo-oophorectomy. Premenopausal bilateral salpingo-oophorectomy may cause adverse events, including dyslipidemia. Gynecologists have to care dyslipidemia in endometrial cancer survivors at cancer follow-up clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Therefore, the prevention of these diseases may lead to an improved QOL for EC survivors as well as post-menopausal women in general. TG levels are elevated in EC patients (1). Furthermore, we confirmed that OP occurs more frequently in non-EC hypercholesterolemia patients.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Therefore, the prevention of these diseases may lead to an improved QOL for EC survivors as well as post-menopausal women in general. TG levels are elevated in EC patients (1). Furthermore, we confirmed that OP occurs more frequently in non-EC hypercholesterolemia patients.…”
Section: Discussionsupporting
confidence: 80%
“…Some studies have reported an association between EC and the risk of dyslipidemia (1,12,19). These findings suggest that common metabolic abnormalities may act to increase dyslipidemia, OP and EC risk, but detailed data on the pathways connecting these conditions are limited.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that higher prevalence of hypertension in patients with endometrial carcinoma could again be related to hyperinsulinemia and insulin resistance [5]. In a recent study, hypertension, diabetes, glucose levels and the consumption of high-glycemic load foods have been found to be positively associated with endometrial cancer risk only among overweight or obese women [25]. In consistency with that finding, the prevalence of hypertension and diabetes were detected higher among the women with cancer and hyperplasia.…”
Section: Discussionmentioning
confidence: 77%